PRODUKTIVITAS DAN EFISIENSI PRODUKSI GONDORUKEM DI BEBERAPA PABRIK DI JAWA TENGAH Productivity and Efficiency of Several Collophonium Factories in Central Java - Sylviani Sylviani (Jurnal Penelitian Hasil Hutan, 1990)
Collcfohonium industries   in  Cen'tralJava are potential  enough to be developed •   a• source of income for people liuirw near the forest  a  well a  for Perum Perhutani.Bated  on the study at several collophonium factories, the averagelabourproductivity for administl'ativelab(!urandtechnician were 742  ton/man and 121,8 tori/man rapeetively.                                                                                      Jlaclainaryeflkiency averageWal    72 %, and that for        material Wal,    189 %. The avm11te ef'/fciency for Coat used by private tac,torywaa 1,86 and.for Perum Perhutani 1,83. Actual total ~ost spent were Rp. 83,886,288   and Rp. 90,27'!,158,ctively,     for factories run by private sector and Perum Perhutani.